TECHNOLOGICAL COMPLEX OF EQUIPMENT FOR REFINING AND CASTING OF STEEL AND ALLOYS IN THE FOUNDRY AND STEEL INDUSTRIES - V. I. Zolotukhin; E. I. Gordeev; A. G. Golovko; D. A. Provorotov (Литьë и металлургия)
Vulcan TM is a small innovative company, specializing in the manufacture of steel and alloys casting systems and refractory accessories.Available for foundry and metallurgical industries, special technological equipment, designed and manufactured by LLC NPP “Vulkan-TM.”